Investigation of Static and Dynamic Load Analysis in the Multi -Machine Wind Farms Using UPFC - Dosoglu, M. K.; Tosun, S.; Guvenc, U.; Ozturk, A. (Elektronika ir Elektrotechnika, 2012)
In this study, static and dynamic load analysis of wind farm examined by using Unified Power Flow Controller (UPFC) that known as one of the Flexible AC Transmission System devices (FACTS). In the wind farm examined, 12 MW Double Feed Induction Generator (DFIG) is used. According to variations of the static and dynamic loads at different times, voltage, active power, reactive power and capacitor voltage of load busses were examined. As a result of this study in case of any instability, UPFC were found to be effective and successful for eliminating instability in a very short period of time. Ill. 20, bibl. 22, tabl. 1 (in English; abstracts in English and Lithuanian). DOI: http://dx.doi.org/10.5755/j01.eee.117.1.1054